2018
DOI: 10.3390/metabo8030043
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Methodological Protocol to Characterize PDO Olive Oils

Abstract: An analytical approach including Panel Test, Isotope Ratio Mass Spectrometry (IRMS) and Nuclear Magnetic Resonance (NMR) spectroscopy was proposed to characterize Italian “Colline Pontine” PDO olive oils (40 samples) of two consecutive crop years. Our approach has evidenced the high quality of these olive oils. Only 6 of 40 olive oils samples were defined as “defective” by the official Panel Test due to the detection of negative sensory attributes. The low variability of isotopic data monitored by IRMS confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Studies of authenticity have been reported for the classification of olive oils according to their botanical or geographical origin, based on determination of fatty acid (FA) profile or minor constituents, as phytosterols, phenols, or volatiles [11,12,13]. In addition, the classification was performed using a simultaneous combination of two or more components; for example nuclear magnetic resonance (NMR) [14], Fourier Transform Infra-Red spectroscopy [15], and stable isotopic techniques [16,17] have been used.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of authenticity have been reported for the classification of olive oils according to their botanical or geographical origin, based on determination of fatty acid (FA) profile or minor constituents, as phytosterols, phenols, or volatiles [11,12,13]. In addition, the classification was performed using a simultaneous combination of two or more components; for example nuclear magnetic resonance (NMR) [14], Fourier Transform Infra-Red spectroscopy [15], and stable isotopic techniques [16,17] have been used.…”
Section: Introductionmentioning
confidence: 99%
“…test). [186][187][188] Although olive oil has been extensively studied all around the world, some metabolites remain unidentified, and the phytochemical composition is a particularly interesting research field. In particular, in our laboratory tetrahydrogeranylgeraniol and dihydrogeranylgeraniol were identified for the first time in both total aliphatic alcohol and waxy fractions of extra virgin olive oil by means of GC and GC-MS methodologies.…”
Section: Silvia Cammaronementioning
confidence: 99%
“…1,2-DAG isomers are commonly attributed to the incomplete biosynthesis of TAGs in olive fruit, whereas 1,3-DAGs are considered to derive mainly from enzymatic or chemical hydrolysis of TAGs before or during oil extraction [12]. It was shown that 1,2-, 1,3-, and total DAG concentrations in olive oil significantly increase as a result of alterations during processing, including, for example, prolonged storage of piled olives before processing [12,51]. During storage 1,2-species isomerize to more stable 1,3-DAGs, making the ratio of 1,3-/1,2-DAG a useful criterion indicative of olive oil age [12,44,51].…”
Section: H-nmr Analysis Of Lipidsmentioning
confidence: 99%
“…It was shown that 1,2-, 1,3-, and total DAG concentrations in olive oil significantly increase as a result of alterations during processing, including, for example, prolonged storage of piled olives before processing [12,51]. During storage 1,2-species isomerize to more stable 1,3-DAGs, making the ratio of 1,3-/1,2-DAG a useful criterion indicative of olive oil age [12,44,51]. In this study, a higher proportion of 1,2-DAG fraction was found in commercially-blended than in PDO EVOO (Table 4), while 1,3-DAG isomers were not identified.…”
Section: H-nmr Analysis Of Lipidsmentioning
confidence: 99%